Performance Analysis of Stock Portfolios Incorporated in IDX30 Using the Sharpe, Treynor and Jensen Method in 2016-2020 - Selvyna Ougesa Claransia; Totok Sugiharto (Institute of Computer Science (IOCS), 2021)
This study aims to determine whether or not there is a difference between the Sharpe, Treynor, and Jensen methods in measuring the optimal IDX30 portfolio. This study uses the One Way of Variance by Rank Kruskal Wallis test. In this study, the values ​​of Sharpe, Treynor, and Jensen were standardized through the Zscore transformation (standardized) followed by the Mean Rank difference test between treatments to determine which index performance was the most consistent. The test results using the Kruskal Wallis test obtained x2 = 0.850, with a probability of 0.654. It is known that the test probability 0.05. These results indicate that there is no significant difference between the tests using the Sharpe, Treynor, and Jensen methods. Thus, the null hypothesis H0 in this study is accepted. The results of the test between the three treatments, the difference between the three mean ranks, showed that there was no significant difference between each treatment because the difference was not that far away. The Treynor method has the lowest mean rank difference between Sharpe and Jensen, meaning that Treynor is the most consistent with non-difference.